Going to the Dogs : Greyhound Racing, Animal Activism, and American Popular Culture - Thayer, Gwyneth Anne (Book collections on Project MUSE., 2013)
A cultural history of greyhound racing in American, charting the sport's meteoric rise, and equally meteoric decline, against the backdrop of changes in American culture during the 20th century.